The Role of Brown Adipose Tissue in the Development and Treatment of Nonalcoholic Steatohepatitis: An Exploratory Gene Expression Study in Mice - De Munck, Toon J.I.; Xu, Pan; Vanderfeesten, Brechtje L.J.; Elizalde, Montserrat; Masclee, Ad A.M.; Nevens, Frederik; Cassiman, David; Schaap, Frank G.; Jonkers, Daisy M.A.E.; Verbeek, Jef (Hormone and Metabolic Research, 2020)
Brown adipose tissue (BAT) might be a beneficial mediator in the development and treatment of nonalcoholic steatohepatitis (NASH). We aim to evaluate the gene expression of BAT activity-related genes during the development and the dietary and surgical treatment of NASH. BAT was collected from male C57BL/6J mice that received a high fat-high sucrose diet (HF-HSD) or a normal chow diet (NCD) for 4 and 20 weeks (n=8–9 per dietary group and timepoint) and from mice that underwent dietary intervention (return to NCD) (n=8), roux-en-y gastric bypass (RYGB) (n=6), or sham procedure (n=6) after 12 weeks HF-HSD. Expression of BAT genes involved in lipid metabolism (Cd36 and Cpt1b; p<0.05) and energy expenditure (Ucp1 and Ucp3; p<0.05) were significantly increased after 4 weeks HF-HSD compared with NCD, whereas in the occurrence of NASH after 20 weeks HF-HSD no difference was observed. We observed no differences in gene expression regarding lipid metabolism or energy expenditure at 8 weeks after dietary intervention (no NASH) compared with HF-HSD mice (NASH), nor in mice that underwent RYGB compared with SHAM. However, dietary intervention and RYGB both decreased the BAT gene expression of inflammatory cytokines (Il1b, Tnf-α and MCP-1; p<0.05). Gene expression of the batokine neuregulin 4 was significantly decreased after 20 weeks HF-HSD (p<0.05) compared with NCD, but was restored by dietary intervention and RYGB (p<0.05). In conclusion, BAT is hallmarked by dynamic alterations in the gene expression profile during the development of NASH and can be modulated by dietary intervention and bariatric surgery.
Keywords: nonalcoholic fatty liver disease, NAFLD, Nrg4, Ucp1, obesity